2007
DOI: 10.1038/sj.cgt.7701029
|View full text |Cite
|
Sign up to set email alerts
|

The proteasome inhibitor bortezomib acts differently in combination with p53 gene transfer or cytotoxic chemotherapy on NSCLC cells

Abstract: In this report, the effects of a combined treatment with the proteasome inhibitor bortezomib and either a recombinant adenoassociated virus type 2 (rAAV-2)-mediated p53 gene transfer or chemotherapeutic agents, docetaxel and pemetrexed, were tested on p53 positive and p53negative non-small cell lung cancer (NSCLC) cell lines. The combination of bortezomib and rAAV-p53 led to a significant synergistic inhibition of cell growth between 62-82% depending on the p53 status of the cell line and drug concentration. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Neukirchen et al demonstrated a significant reduction in growth inhibition and apoptosis when bortezomib and docetaxel or pemetrexed were administered simultaneously. This indicates antagonism between these combinations, possibly due to bortezomib-mediated G2/M arrest preventing cells from entering the stage of the cell cycle at which docetaxel or pemetrexed have cytotoxic activity [40]. Conversely, Gordon et al showed that, bortezomib increases the cytotoxicity of pemetrexed in malignant pleural mesothelioma cell lines in a concentration-dependent manner when administered prior to pemetrexed [41].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Neukirchen et al demonstrated a significant reduction in growth inhibition and apoptosis when bortezomib and docetaxel or pemetrexed were administered simultaneously. This indicates antagonism between these combinations, possibly due to bortezomib-mediated G2/M arrest preventing cells from entering the stage of the cell cycle at which docetaxel or pemetrexed have cytotoxic activity [40]. Conversely, Gordon et al showed that, bortezomib increases the cytotoxicity of pemetrexed in malignant pleural mesothelioma cell lines in a concentration-dependent manner when administered prior to pemetrexed [41].…”
Section: Discussionmentioning
confidence: 95%
“…Recent preclinical data have shown that bortezomib and pemetrexed in combination can be both antagonistic [40] and synergistic [41]. Neukirchen et al demonstrated a significant reduction in growth inhibition and apoptosis when bortezomib and docetaxel or pemetrexed were administered simultaneously.…”
Section: Discussionmentioning
confidence: 96%
“…Despite variances in toxicity rates, similar levels of cell death-associated nucleosomes were measured following treatment with the two drugs, thereby indicating the varying efficacy in blocking cell proliferation and apoptosis induction. In addition, the current findings confirm that cytoplasmic nucleosomal fragments are useful tools for evaluating apoptosis in intact cells, as DNA degradation occurs several hours before plasma membrane breakdown during the apoptotic process (21). The primary goal of the present study was to investigate GAS5 accumulation in exosomes during apoptotic induction triggered by two different mechanisms, e.g., microtubule stabilization and DNA strand breaks.…”
Section: Mean Cell Index (% Of Control)mentioning
confidence: 96%
“…In addition to reducing the activation state of NF-κB by inhibiting proteasomal degradation of IκB, PS-341 affects many other pathways and targets, leading to high expression levels of several proapoptotic proteins in certain experimental conditions. 23 In vitro, PS-341 has been found to enhance antitumor cell effects of select chemotherapeutic agents 6,24 , tumor cell targeting antibodies 25 , and ionizing radiation 26 . Yet, little is known about the combined effects of PS-341 and ionizing radiation on normal cells and tissues of vertebrate organisms.…”
Section: Proteasome Inhibitors Radiosensitize Zebrafish Embryosmentioning
confidence: 99%